Genderized Implications of Bride Pricing Culture in Igbo Land - Oboko, Uche Gloria; Ifeanyichukwu, Aloysius Ebuka (Lingual Journal of Language and Culture; Vol 12 No 2 (2021): Lingual: Journal of Language and Culture, 2021)
The study aims at ascertaining the actual implication of bride pricing system in traditional marriages in Igbo land. A total of fifty respondents (thirty women and twenty men) from the five states that make up the southeast zone in Nigeria were selected for the study. Being a qualitative research, the study adopted the ethnographic research design and employed a purposive non-probability sampling method in selecting the respondents. The study made use of focused group discussions, unstructured interview and participants’ observation method as instruments of data collection. The collection of data lasted for a period of six months from June 2020 to November 2020. The research is anchored on Radical and Snail sense Feminism theories and data for the study were analysed using descriptive thematic method. Findings from the study reveal that payment of bride price does not reduce women to mere commodities in Igbo land. It also reveals that it gives undue privileges to men in Igbo land among other findings.  Finally, it was shown that Igbo men and women still regard bride price payment as an important aspect of their culture which should not be abolished.